Treatment of Severe Tumoral Calcinosis with Teriparatide in a Dialysis Patient after Total Parathyroidectomy - Ho-Kwan Sin; Ping-Nam Wong; Kin-Yee Lo; Man-Wai Lo; Shuk-Fan Chan; Kwok-Chi Lo; Yuk-Yi Wong; Lo-Yi Ho; Wing-Tung Kwok; Kai-Chun Chan; Andrew Kui-Man Wong; Siu-Ka Mak (Case Reports in Nephrology)
Tumoral calcinosis is a rare but debilitating condition that can affect dialysis patients. Optimal management is largely unknown. We report the clinical course, treatment, and outcome of a peritoneal dialysis (PD) patient who developed tumoral calcinosis refractory to conventional treatment but improved with teriparatide therapy. A 26-year-old lady on PD for 2 years presented to us with tumoral calcinosis involving bilateral hands. Response to surgical excision, parathyroidectomy, and conversion to hemodialysis failed to result in sustained remission, and tumoral calcinosis progressed. After total parathyroidectomy, the patient had transient but partial remission in which her calcinosis deposits remained but were asymptomatic without pain or clinical signs of inflammation. However, she later experienced a relapse with involvement of the left elbow, right shoulder, right hip, and right thigh. Tumoral calcinosis remained uncontrolled resulting in debilitation, likely attributable to poor calcium and phosphate control because of adynamic bone disease after parathyroidectomy despite treatment of superimposed tuberculosis and therapy with sodium thiosulphate and pamidronic acid. Clinical improvement was however evident after the use of teriparatide. Asymptomatic hypocalcemia occurred after teriparatide therapy but resolved after 2 months. In conclusion, teriparatide appears to be useful for treating tumoral calcinosis in the presence of adynamic bone disease. Hypocalcemia can occur in the initial months of therapy.